PENGARUH LITERASI DIGITAL DAN LITERASI INFORMASI TERHADAP PENINGKATAN INDEKS PRESTASI KUMULATIF (IPK) MAHASIWA DI KOTA SINTANG - Adung Adung; Yulia Suriyanti; Yopinus Bobi (STKIP Persada Khatulistiwa Sintang, 2025)
This research is motivated by the importance of mastering digital literacy and information literacy as essential skills for students in their academic journey. The aim of this study is to determine the influence of Digital Literacy and Information Literacy on the improvement of Grade Point Average (GPA) among university students in Sintang City. This study uses a quantitative approach with multiple linear regression methods. Data were collected through questionnaires and analyzed using regression techniques.The results show that both Digital Literacy and Information Literacy have a significant partial effect on GPA, as indicated by the t value of Digital Literacy at 2.560 > t table 1.649 and a significance value below 0.05. Simultaneously, both variables also significantly affect GPA with a significance value of 0.000 < 0.05 and an F value of 3.398 > F table 3.02. The most dominant variable influencing GPA is Information Literacy, with a regression coefficient of 0.015, compared to Digital Literacy, which is 0.011.The findings of this study are expected to serve as a foundation for developing learning strategies in higher education and as a reference for lecturers and policymakers to improve students' GPA through strengthening digital and information literacy.